Innovative Strategies for Restoration of Degraded Ecosystems: A Case Study of Abandoned Agricultural Land and Abandoned Mining Land Recovery in West Java Province - Muhammad Adam Suni; Busranuddin Daeng Masserang; Agung Dwi Kurniawan; Mohamad Fahrul Himalaya Umar; Yohanis Toding (West Science Nature and Technology, 2023)
Ecosystem degradation and land abandonment are pressing global environmental challenges, with significant ecological, social, and economic consequences. In the context of West Java Province, Indonesia, the degradation of abandoned agricultural and mining lands has been a particularly pronounced issue. This study explored innovative strategies for the restoration of these degraded ecosystems, focusing on the recovery of abandoned agricultural and mining lands in West Java. The research employed a mixed-methods approach, combining quantitative and qualitative data collection methods. Key findings revealed a range of innovative strategies, including natural regeneration, agroforestry, phytoremediation, and soil improvement techniques, being used to restore abandoned lands. Challenges such as slow ecological recovery, community conflicts, and technical hurdles were also identified. Despite these challenges, the restoration efforts have yielded positive ecological, social, and economic outcomes, including increased biodiversity, improved soil quality, enhanced community livelihoods, and economic benefits. This study provides valuable insights into the complex process of ecosystem restoration in West Java Province and offers recommendations for policymakers, landowners, and conservation practitioners. The findings underscore the importance of community engagement, sustainable land management practices, and ongoing monitoring and research to support the long-term success of ecosystem restoration initiatives.